2007
DOI: 10.1016/j.drugpo.2006.12.011
|View full text |Cite
|
Sign up to set email alerts
|

HIV treatment access and scale-up for delivery of opiate substitution therapy with buprenorphine for IDUs in Ukraine—programme description and policy implications

Abstract: Background-Injection drug use (IDU) accounts for 70% of HIV cases in Ukraine. Until buprenorphine maintenance therapy (BMT) was introduced, few effective strategies aimed at achieving reduction in illicit drug use were available as a conduit to antiretroviral therapy (ARV) among IDUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 4 publications
3
60
0
1
Order By: Relevance
“…In June 2007, methadone was approved by the Ukrainian Ministry of Health and will now also be made available for maintenance treatment. Nevertheless, the number of IDUs receiving agonist maintenance is still very low and the vast majority of IDUs have not yet been reached by OST [4] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In June 2007, methadone was approved by the Ukrainian Ministry of Health and will now also be made available for maintenance treatment. Nevertheless, the number of IDUs receiving agonist maintenance is still very low and the vast majority of IDUs have not yet been reached by OST [4] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the low availability of agonist maintenance in the Ukraine, access to antiretroviral therapy (ART) for IDUs was and still is low, and clinicians have tended to refuse ARTs to active IDUs, believing that they would be poorly adherent [4] . However, recent evidence has emerged that integrating ART and OST in HIV-positive IDUs can optimize outcomes for both opiate addiction and HIV infection status [7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though buprenorphine maintenance treatment was started earlier in Ukraine (Bruce, Dvoryak, Sylla, & Altice, 2007), MMT began in 2008, and the first MMT program integrated into a TB-facility was launched in 2009. Out of 109 inpatient TB clinics in Ukraine, only 11 provide MMT, with the majority having only a few clients each.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid substitution therapy (OST) using buprenorphine and methadone has been introduced in some Former Soviet States including Ukraine (Bruce, Dvoryak, Sylla, & Altice, 2007;Dvoriak et al, 2013;Dvoryak & Grishayeva, 2008;Golovanevskaya, Vlasenko, & Saucier, 2012;Lawrinson et al, 2008) and Georgia (Gambashidze, Sikharulidze, Piralishvili, & Gvakharia, 2008;Otiashvili et al, 2010;Piralishvili, Gamkrelidze, Nikolaishvili, & Chavchanidze, 2012) and data are becoming available on its effectiveness in these cultural settings. Findings from the U.S., Western Europe, and Australia have consistently found that OST is associated with substantial reductions in illicit opioid use, criminal activity, and drug related mortality, and that it can play an important role in reducing the spread of HIV by reducing injection risk and improving adherence to antiretroviral therapy (Cornish, Macleod, Strang, Vickerman, & Hickman, 2010;Degenhardt et al, 2010;Gowing, Farrell, Bornemann, Sullivan, & Ali, 2011;Kimber et al, 2010;MacArthur et al, 2012;Malta, Strathdee, Magnanini, & Bastos, 2008;Mattick, Breen, Kimber, & Davoli, 2003;Mattick, Breen, Kimber, & Davoli, 2007;Suntharasamai et al, 2009;Tilson et al, 2007).…”
Section: Introductionmentioning
confidence: 97%